Die Auswirkungen der Subprime-Krise auf den deutschen LBO-Markt für Small- und MidCaps - Christina E. Bannier; Stefan Müsch (Frankfurt School of Finance & Management, 2008)
Since summer 2007 the Subprime credit crisis has been affecting the international financial markets. One of the consequences of the crisis was the collapse of the market for large-sized leveraged buyout transactions in late 2007 and early 2008. The goal of this Working Paper is to examine to what extent also small and mid-sized LBO deals in Germany were affected by the market turbulences. After illustrating the aspects of the crisis which are relevant for this topic, six hypotheses regarding potential consequences of the crisis on the German LBO market for Small-and MidCaps were set up. To verify these hypotheses a survey among the market participants, namely financing banks and LBO investors, was conducted in May and June 2008.
urn:nbn:de:101:1-20081028264
Keywords: 330; LBO; Subprime; Krise; KMU; Buyout; Leveraged Buyout; Finanzinvestoren; Private Equity